2009
DOI: 10.1021/jp9080492
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-Functionalized Gold Nanodots: Two-Photon Absorption Property and Imaging In Vitro

Abstract: We report here the study of two-photon induced luminescence of 11-mercaptoundecanoic acid functionalized quantum-sized Au nanodots (11MUA-Au nanodots). The X-ray absorption near-edge structure (XANES) measurement at the gold L III edge indicates that the oxidation state of the surface of 11MUA-Au nanodots is best described as Au + . The two-photon absorption (TPA) property of 11MUA-Au nanodots was then investigated via an open aperture Z-scan method. Together with a precise extinction coefficient (i.e., onepho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 96 publications
(31 reference statements)
1
45
1
Order By: Relevance
“…By contrast, featureless absorption spectra are observed for the solutions prepared at lower pH values. This fact indicates that the fluorescent Au NCs produced at the weakly acidic conditions should be smaller than 2 nm in diameter [57,58], which is in agreement with the TEM results and the Jellium model-based prediction. Previously, the similar absorption spectra with such featureless behaviors were observed for fluorescent Au NCs by their intensities decaying roughly exponentially toward the visible region from the UV region [14,36,38,39].…”
supporting
confidence: 87%
“…By contrast, featureless absorption spectra are observed for the solutions prepared at lower pH values. This fact indicates that the fluorescent Au NCs produced at the weakly acidic conditions should be smaller than 2 nm in diameter [57,58], which is in agreement with the TEM results and the Jellium model-based prediction. Previously, the similar absorption spectra with such featureless behaviors were observed for fluorescent Au NCs by their intensities decaying roughly exponentially toward the visible region from the UV region [14,36,38,39].…”
supporting
confidence: 87%
“…Two photon‐based bioimaging has more advantage over conventional single‐photon imaging, because it can image deeper tissue and efficiently suppress background signal. Dextran functionalized, mercaptoundecanoic acid capped FGCs have been used to label human mesenchymal stem cells and two‐photon imaging under 800 nm excitation shows bright green emission due to FGCs . Glutathione protected FGCs are reported to have higher two photon cross‐section efficiency than mercaptoundecanoic acid capped FGCs .…”
Section: Development Of Gold Nanoclusters Based Bioimaging Probesmentioning
confidence: 99%
“…Gold nanorods have proven to be an effective fluorescent agent for imaging a variety of biological species, such as cancer cells [392][393][394], Bacillus spores [395], and mesenchymal stem cells [396]. Wang et al demonstrated that gold nanorods possess strong TPL intensities with a cos 4 dependence on the incident polarization [397].…”
Section: Two-photon Luminescence Microscopymentioning
confidence: 99%